KERAGAMAN JENIS RAYAP PADA PERUMAHAN DI KABUPATEN SIGI SULAWESI TENGAH - Hapid, Abdul; Ariyanti, Ariyanti; Zulkaidhah, Zulkaidhah (ForestSains, 2017)
Termite control activities in Indonesia, particularly in Central Sulawesi until the moment still confront obstacles in the forms not yet complete information on the diversity of the termite itself and knowledge of the characteristics bioecology and habit in this spread. This is the cause so far undertaken control measures are still limited to the spraying of chemicals that require high costs and have negative impacts on the environment and the potential to kill organisms that are beneficial. This study was aimed known the diversity of termitesattacking in the buiding Sigi District, Central Sulawesi.The study wasconducted at termite habitat. These termite sample were collected by getting baitting method and direct taking of the habitat of termites, which continued with the identification of activities for determining the types of termites. The result showed that there are six genera of termites from  15  Subdistrict  in  Sigi  District  were  Microcerotermes,  Odontotermes,  Nasutitermes, Schedorhinotermes dan Parrhinotermes.